Psychological well-being and spiritual intelligence as predictors of suicidal ideation among emerging adults in Malaysia - Foo, Suh Jin; Lo, Kah Wah (2018)
Suicide behaviour is one of a worrisome issue in Malaysia which this country has medium rate of high suicide rate among Southeast Asia nations. Therefore, the study was aimed to understand psychological well-being and spiritual intelligence as predictors of suicidal ideation among emerging adults in Malaysia. A total of 304 samples were recruited but only 271 samples were involve into actual study to answer questionnaire through online and pencil-and-pen method. The Scale of Suicidal ideation (SSI), Ryff’s Psychological WellBeing Scale-42 items and Spiritual Intelligence Self-Report Inventory-24 items were employed in this study. Data collected was interpreted using the Statistical Package for Social Science (SPSS) software version 25.0. Three-Step Theory to achieve the objective to understand the relationship between psychological well-being and spiritual intelligence toward suicidal ideation. Results of pearson correlation showed that there was a significant negative correlation between suicidal ideation and psychological well-being while significant positive correlation between suicidal ideation and spiritual intelligence. Results of multiple linear regression found out psychological well-being and spiritual intelligence statistically predicted suicidal ideation. Spiritual intelligence best predicted suicidal ideation. Implications and limitations of this study were discussed and recommendations for future studies were made.